Sedimentary record of plutonium in the North Yellow Sea and the response to catchment environmental changes of inflow rivers. (September 2018) - Xu, Yihong; Pan, Shaoming; Gao, Jianhua; Hou, Xiaolin; Ma, Yongfu; Hao, Yongpei
Abstract: Plutonium (Pu) isotopes were first determined in surface and core sediment samples collected from the northern North Yellow Sea (NYS) to elucidate their source terms and deposition process as well as the response to catchment environmental changes of inflow rivers. 240 Pu/ 239 Pu atom ratios in all sediments showed the typical global fallout value of ∼0.18 without any influences from the nuclear weapons tests conducted recently in the North Korea or early in the Pacific Proving Ground. The large variation of 239+240 Pu activities (0.022–0.515 mBq/g) observed in surface sediments should be mainly attributed to the re-suspension and transportation of fine sediments influenced by the Liaonan Costal Current. Based on the two 239+249 Pu depth profiles with easily observed onset fallout levels (1952) and global fallout peaks (1963), 239+240 Pu served as a valid time mark in the coastal sedimentary system. Riverine input Pu contributed only 15–27% to the total global fallout inventory (92.5–108.8 Bq/m 2 ) in the northern NYS, much lower than that in the Yangtze River estuary (77–80%), indicating a better soil conservation in the northeast China due to higher forest coverage compared to the Yangtze River's drainage basin. The increase of riverine input Pu after 1980s reflected the more intense soil erosion degree caused by the land use and cover change due to the increment of human activities in the northeast China at the same period. Our results demonstrated that plutonium is a good indicator for studying sedimentary process and its response to the environment in the coastal area. Graphical abstract: Image 1 Highlights: Sedimentary records of Pu reflected well the catchment environmental changes. The atmospheric fallout is the dominant source of Pu in the North Yellow Sea. PPG-derived Pu has no significant influence on the North Yellow Sea. Pu is a good chronological tracer for studying modern costal sedimentary process. Pu inventories indicated the riverine input source other than the direct deposition.